PENGARUH MOTIVASI KERJA DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU YANG DIMEDIASI OLEH SELF EFFICACY STUDI PADA GURU SMP NEGERI SEKECAMATAN BATANG KABUPATEN BATANG - Suningsih, 12 5202 0255; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze the effect of work motivation, professional competence and self-efficacy on teacher performance and the role of self-efficacy mediates the influence of motivation and professional competence of the teachers performance in the junior high school teachers in the Batang subdistrict, Batang districk. The population in this study was a Junior High School teacher in Batang subdistrict numbered 238 people. Because the population is large, then made amodel of sampling with purposive sampling method, that is sampling with certain criteria. In this case the researchers used a sample of teacher from who have received certification allowance amounting to 131 people. Then from 131 people,who returns the questionnaire answers amounted to 131 people. The results showed that (1) work motivation has positive effect and significant on self-efficacy, (2) professional competence is also has positive and not significant effect on self-efficacy, (3) work motivation has no positive and not significant impact on teacher performance, (4) professional competence positive and not significant impact on teacher performance, (5) self-efficacy and significant positive impact on teacher performance, (6) self-efficacy mediates the effect of motivation to work on teacher performance, (7) self-efficacy does not mediate the effect of the professional competence of the teachers performance. Keywords: work motivation, professional competence, self-efficacy and teacher performance.